Sarakhsi’s Doctrine of Juristic Preference (Istihsan) as a Methodological Approach Toward Worldly Affairs (Ahkam al-Dunya) (American Journal of Islam and Society, 1988)
In the present investigation, we shall develop systematically Sarakhsrsdoctrine of Juristic preference from his Mabsut, Usul and Bab al-Muwada'aof Sharh al-Siyar al Kabir and demonstrate how Sarakhsi establishes itsrelevance as a methodological approach toward worldly affairs.The investigation is carried out in four parts:In the first part, we shall relate Sarakhsi’s doctrine of juristic preference(istihan) with his concept of treaties (muwada'a). According to Sarakhsimuwada'a is an autonomous discipline and its main focus is worldly affairsas relations (muamalat) of Muslims with other nations.In the second part, it is investigated how Sarakhsi strives to see thejustification for the application of the doctrine of juristic preference to itindependently of the doctrine of systematic reasoning (qiyas) by establishingthe ’illa (effective reasoning) of the doctrine of juristic preference on the basisof asl derived from the Qur’an and Hadith.In the third part, we shall discuss how Sarakhsi systematizes the doctrineof juristic preference by analyzing the ’illa employed by it in various formsand shows that it is connected with asl.Finally, in the fourth part, we shall show how Sarakhsi justifies theemployment of the doctrine of juristic preference as a methodological approachtoward muwadah and worldly affairs ...